A survey on the implementation of facilities maintenance management system of building in Iran - Amani, Nima (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2012)
The degree of the implementation of building facilities maintenance management (FMM) has a major impact on its performance. As a result, the influence of facilities management on the maintenance of buildings is greater than ever before. The issue related to building maintenance is a universal one and its consideration at the facilities maintenance stage is of great importance on the future performance of the building. This research has been conducted to study the impact of maintenance-related issues on facilities maintenance management system. Building maintenance includes cleaning, inspecting, repairing, and replacing the building’s various systems and components. Questionnaires were distributed in big cities of Iran. The findings identified the level of companies’ knowledge in facilities maintenance-related issues; the degree to which executive staff is exposed to training in facilities maintenance-related matters; the extent to which companies consult maintenance consultants; the relative importance of facilities maintenance (FM) issues to other performance factors and the level of difficulty in cleaning, inspecting, repairing, and replacing various building components. Based on the findings, the main problems related to management of facilities maintenance system of building needs serious attention from the authorities in order to improve the overall maintenance system.